2021
DOI: 10.1007/s00520-021-06422-3
|View full text |Cite
|
Sign up to set email alerts
|

Distress among cancer patients attending rehabilitation in the community

Abstract: Purpose The aim of this study is to identify sources of distress among cancer patients attending rehabilitation in the community. Methods Participants were 430 patients recruited from a cancer rehabilitation center in Singapore between 2017 and 2018, who had rated their distress using the distress thermometer (DT) and indicated associated problems on the problem list. Chi-square tests were used to detect differences in the reported symptoms among three age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
1
4
1
Order By: Relevance
“…We also report a mean distress level of 3.51, which is similar to an earlier study in Singapore, which reported a mean distress level of 3.3 [ 20 ]. Nearly 2/3 of our study population experiencing significant distress, which is in line with a reported worldwide prevalence rate of 20–52% of cancer patients [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We also report a mean distress level of 3.51, which is similar to an earlier study in Singapore, which reported a mean distress level of 3.3 [ 20 ]. Nearly 2/3 of our study population experiencing significant distress, which is in line with a reported worldwide prevalence rate of 20–52% of cancer patients [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…Unsurprisingly, distress has been shown to be strongly associated with mood disturbances including stress, anxiety, and depression which may not reach the criteria for clinical diagnosis, but still interfere with HRQOL [ 45 , 46 ]. Our findings emphasize the need to consistently screen for social and emotional issues in cancer survivors, even while many of these patients are undergoing physical therapy-based rehabilitation [ 20 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the literature, a correlation between the domains or items of the Problem List and the distress score on the DT has often been found, although not equally for every patient group and every item. 27,28 Despite the fact that we found no significant between-group differences in terms of distress, the finding that more than half of the parents report increased distress is highly relevant because it can result in negative consequences for the children. In a U.S. national survey, Amrock et al found a correlation between parental distress and children's mental health.…”
Section: 23%contrasting
confidence: 71%
“…Among Chinese persons with cancer, 20% reported elevated psychological distress (Rao et al, 2019). Among individuals attending a cancer rehabilitation facility in Singapore, approximately 30% reported distress in the elevated range (Kuo, 2022). Among South African persons with cancer, more than 33% of study participants had high scores on the Center for Epidemiological Studies – Depression Scale (CESD) and the Hopkins Symptom Checklist, which correlated with perceived social support and body change stress (Kagee et al, 2018).…”
mentioning
confidence: 99%